Comparing the effects of left bundle branch pacing and leadless right ventricular pacing on intraventricular and interventricular dyssynchrony using in silico modelling - Liew, Alphonsus; Strocchi, Marina; Rodero, Cristobal; Gillette, Karli K.; Wijesuriya, Nadeev; Howell, Sandra; de Vere, Felicity; Vigmond, Edward J.; Plank, Gernot; Niederer, Steven; Rinaldi, Christopher Aldo (Frontiers in Physiology, 2025)
IntroductionNon-physiological right ventricular pacing (RVP) is currently the mainstay of treatment for patients with high-degree atrioventricular (AV) block who have preserved left ventricular ejection fraction. Newer pacing strategies, such as left bundle branch pacing (LBBP) and leadless cardiac pacemakers (LCPMs), are increasingly being adopted due to their respective advantages over RVP. However, there has been no direct comparison between LCPMs and LBBP regarding their risk of pacing-induced cardiomyopathy, which is thought to arise from interventricular and intraventricular dyssynchrony. Using in silico modelling, we compared the effects of LBBP and LCPMs on interventricular and intraventricular synchrony.MethodsUsing 19 four-chamber healthy heart geometries, we simulated LCPMs at the level of the right ventricular outflow tract-septum (RVOT-S), mid-septum (MS), and apical septum (AS), along with proximal left bundle pacing (PLBBP) and distal left bundle pacing (DLBBP) in 3 different settings: 1) intact left bundle branch conduction, 2) left bundle branch block (LBBB), and 3) septal scar involving the His-Purkinje system (HPS). Ventricular electrical uncoupling (VEU), absolute VEU, and left ventricular dyssynchrony index (LVDI) were measured. The shortest interval required to activate 90% of both ventricles (BIVAT-90) was also recorded.ResultsIn the setting of intact left bundle branch conduction, combined LBBP configurations had significantly lower VEU (LBBP: −3.3 ± 5.1 vs. LCPM: 24.2 ± 7.6 ms, p < 0.01) and absolute VEU (LBBP: 5.0 ± 3.5 vs. LCPM: 24.2 ± 7.6 ms, p < 0.01) than combined LCPM configurations. In the presence of proximal LBBB, combined LBBP configurations also had significantly lower VEU (LBBP −22.1 ± 0.5 vs. LCPM 25.9 ± 7.9, p < 0.01) and absolute VEU (LBBP 22.1 ± 0.5 vs. LCPM 25.9 ± 7.9 ms, p < 0.01) than combined LCPM configurations. However, there was no significant difference in absolute VEU when combined LBBP configurations was compared with RVOT-S configuration alone (LBBP 22.1 ± 0.5 vs. RVOT-S 21.7 ± 9.0 ms, p = 0.86). In the presence of septal scar, combined LCPM configurations had significantly lower VEU compared with combined LBBP configurations (VEU: LCPM 31.0 ± 8.4 vs. LBBP 41.7 ± 20.2 ms, respectively; p < 0.01). Combined LBBP configurations had significantly lower LVDI and BIVAT-90 compared with combined LCPM configurations in both the presence and absence of LBBB, but there was no significant difference between the two in the setting of a septal scar.ConclusionLCPM produces less interventricular dyssynchrony than LBBP in the presence of extensive septal scarring involving the HPS. In the setting of proximal LBBB, LCPM at the RVOT-S level may be non-inferior to LBBP in terms of interventricular dyssynchrony.